Family Counseling Center: Reality and Aspirations: A Field Study at family counseling clinic in the city of Sulaimaniyah - Ghafur, Rzgar (Al-Adab Journal, 2023)
This research aims at  identifying the reality of the  premarital counseling training program at the Family Counseling Clinic in the city of Sulaimaniyah with respect to the legal, health and social aspects measures, and to be aware of the respondents’ opinions about (time and duration of the course, the lecture hall, the capacity of the lecturers in communicating information to the respondents, to educate the respondents about marriage and building up a family) as well as getting to know the aspirations that the respondents have of the premarital counseling training program. Being a descriptive one, the research has employed a social survey method using the sampling technic. The research community consisted of (502) young people of both sexes who were about to get married and who received a premarital counseling training course at the Family Counseling Clinic in Sulaimaniyah during the period from Nov. 1st., 2021 to Nov 20th.,2021. The research sample consisted of (200) males and females. All were randomly selected among those who were about to get married; besides a questionnaire was applied to the study sample in order to achieve the objectives of the research.Consequently, the research has found out the following:1- The results reveal that those who are about to get married have positive opinions concerning the rationality of the legal, health and social premarital measures.2-It also shows that those who are about to get married and have got counseling are satisfied with (the time and duration of the course, the lecture hall, the capacity of the lecturers in communicating information to the respondents, the respondents’ awareness of marriage and preparing for entering their new marital life).3-The results also reveal that all those who are about to get married hope and aspire that the lectures of the premarital counseling training course program will include information about raising and upbringing children. They have also indicated that it is necessary for such a training program to include information about marital disagreements, psychological problems and how to achieve family accord. They also stress the importance of providing the respondents with information on developing marital skills on communication and interactions that help family stability, as well as the importance of training on skills on how to deal with marital disputes.